2018
DOI: 10.1186/s12889-018-5124-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for malnutrition among preschool children in rural Karnataka: a case-control study

Abstract: BackgroundThe prevalence of malnutrition among children in developing countries is very high. As a step towards reducing the prevalence of malnutrition, there is a need to identify the important determinants of malnutrition in the specific population so that preventive and control measures can be implemented.The objective of the study is to determine the risk factors for malnutrition among preschool children in Rural Karnataka, South India.MethodsA case-control study was carried out among preschool children, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
49
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 19 publications
9
49
2
3
Order By: Relevance
“…To evolve as a healthy individual, the infant should be continued with adequate and appropriate safe complimentary food along with breast milk up to two years of age or beyond. 5 In the present study also, similar nding was observed i.e. exclusive breastfeeding up to 6 months acts as a protective factor against underweight among under ve children from a rural area (Adj OR=0.50, p<0.05).…”
Section: Discussionsupporting
confidence: 89%
“…To evolve as a healthy individual, the infant should be continued with adequate and appropriate safe complimentary food along with breast milk up to two years of age or beyond. 5 In the present study also, similar nding was observed i.e. exclusive breastfeeding up to 6 months acts as a protective factor against underweight among under ve children from a rural area (Adj OR=0.50, p<0.05).…”
Section: Discussionsupporting
confidence: 89%
“…In our study finding, educational level of mothers/caregivers and childhood malnutrition were negatively associated in multivariable model. This study finding was inconsistent with studies done in Malaysia, India, and Ethiopia, which stated that mothers/caregivers education has definite and significant effect on nutritional status of children [19,28,29]. This might be due to the fact that even though they have a high educational level, they wouldn't have better practical skills to keep sanitation and hygiene of their children or have no better information to provide an adequate diet to keep the nutritional status of their children.…”
Section: Discussioncontrasting
confidence: 65%
“…Once they were explained nutrients, balanced diet, malnutrition and associated disorders, food safety and hygiene they were very careful with the food given to the children and adopted more sanitary and hygienic practices. Many studies have reported that poor sanitation status, lack of personal hygiene and low socioeconomic statuses have an impact on malnutrition [9].…”
Section: Discussionmentioning
confidence: 99%
“…There are modifiable and non-modifiable factors to malnutrition, out of which the environmental factor is one that can be worked on in a cost effective way. The quality of the future of human resources depends on the children of today [9] we must do everything we can to ensure their optimum health.…”
Section: Discussionmentioning
confidence: 99%